Clinical and functional significance of circular RNAs in cytogenetically normal AML - Papaioannou, Dimitrios (Blood Adv, 2020)
Circular RNAs (circRNAs) are noncoding RNA molecules that display a perturbed arrangement of exons, called backsplicing. To examine the prognostic and biologic significance of circRNA expression in cytogenetically normal acute myeloid leukemia (CN-AML), we conducted whole-transcriptome profiling in 365 younger adults (age 18-60 years) with CN-AML. We applied a novel pipeline, called Massive Scan for circRNA, to identify and quantify circRNA expression. We validated the high sensitivity and specificity of our pipeline by performing RNase R treatment and RNA sequencing in samples of AML patients and cell lines. Unsupervised clustering analyses identified 3 distinct circRNA expression–based clusters with different frequencies of clinical and molecular features. After dividing our cohort into training and validation data sets, we identified 4 circRNAs (circCFLAR, circKLHL8, circSMC1A, and circFCHO2) that were prognostic in both data sets; high expression of each prognostic circRNA was associated with longer disease-free, overall, and event-free survival. In multivariable analyses, high circKLHL8 and high circFCHO2 expression were independently associated with better clinical outcome of CN-AML patients, after adjusting for other covariates. To examine the biologic relevance of circRNA expression, we performed knockdown screening experiments in a subset of prognostic and gene mutation–related candidate circRNAs. We identified circFBXW7, but not its linear messenger RNA, as a regulator of the proliferative capacity of AML blasts. In summary, our findings underscore the molecular associations, prognostic significance, and functional relevance of circRNA expression in CN-AML.